5(b+7)-2=4(b+3)+5

Simple and best practice solution for 5(b+7)-2=4(b+3)+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(b+7)-2=4(b+3)+5 equation:


Simplifying
5(b + 7) + -2 = 4(b + 3) + 5

Reorder the terms:
5(7 + b) + -2 = 4(b + 3) + 5
(7 * 5 + b * 5) + -2 = 4(b + 3) + 5
(35 + 5b) + -2 = 4(b + 3) + 5

Reorder the terms:
35 + -2 + 5b = 4(b + 3) + 5

Combine like terms: 35 + -2 = 33
33 + 5b = 4(b + 3) + 5

Reorder the terms:
33 + 5b = 4(3 + b) + 5
33 + 5b = (3 * 4 + b * 4) + 5
33 + 5b = (12 + 4b) + 5

Reorder the terms:
33 + 5b = 12 + 5 + 4b

Combine like terms: 12 + 5 = 17
33 + 5b = 17 + 4b

Solving
33 + 5b = 17 + 4b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-4b' to each side of the equation.
33 + 5b + -4b = 17 + 4b + -4b

Combine like terms: 5b + -4b = 1b
33 + 1b = 17 + 4b + -4b

Combine like terms: 4b + -4b = 0
33 + 1b = 17 + 0
33 + 1b = 17

Add '-33' to each side of the equation.
33 + -33 + 1b = 17 + -33

Combine like terms: 33 + -33 = 0
0 + 1b = 17 + -33
1b = 17 + -33

Combine like terms: 17 + -33 = -16
1b = -16

Divide each side by '1'.
b = -16

Simplifying
b = -16

See similar equations:

| 7(x-2)=5(3x+1)+5 | | 6-2x=6x+10 | | 4(s+3)-1=3(2s+1)+5 | | x^2-308x+23716=0 | | 7a-6=19+2a | | 2x=x+26 | | 4r^2-18r-100=0 | | x+(2x)=12xy*y^2 | | -5(t-3)-(t+4)=10 | | A=2(L+W)(W) | | A=2(L+W) | | 21+(-47)+12+38+(-54)= | | 6y-12y+3= | | X^4-5x^3+11x^2-25x+30=0 | | c=gm | | (2x-3y)(x+2y)=0 | | 6y+12y+3= | | X-5=(2x-3) | | 25r^3-9r=0 | | 8x+9=4x-5 | | 4x+5=6x | | 3y+4z=16(y+z) | | 6v^2-3v+1=0 | | X-5=2(3-x) | | (4x-8)-(7x+9)= | | x-4y=u | | 5=4m+4u | | 7x-35+14=7 | | (4/5)1.175= | | 3x-(5x-4)= | | 3p^4-18p^3-81p^2= | | 1+x-2x+3x-4x=0 |

Equations solver categories